Pengembangan LKS Berbasis Konteks Lubuklinggau di Tinjau dari Segi Kevalidan dan Kepraktisan - Adha, Idul; Refianti, Rani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
This research was conducted at SMP N 8 Lubuklinggau in the academic year 2019/2020. The purpose of this research is to produce student worksheets (LKS) that are valid and practical using the Indonesian realistic mathematics approach (PMRI). This research refers to development research using a 4-D research model that has been modified to become 3-D. The validity of the LKS that was developed was seen from the results of the validation questionnaire of three experts while the practicality was seen from the results of the practicality questionnaire given to the one to one hold, small group test and large group test. Based on the results of questionnaire validation obtained an average score of 3.13 are in the valid category. Whereas based on practicality testing the LKS that was developed was in the practical category with an average score of 3.25.